Validation of moving target doses using ArcCHECK Planned Dose Perturbation Algorithm (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The aim of the study is to use Planned Dose Perturbation (PDPâ„¢) measurement-guided reconstruction method to estimate dynamic 4D dose and evaluate both 3D dose and DVH changes caused by target motion resulting from respiration. Five patients of Ca lung were selected for the study. Target and Organ at risks were (OARs) delineated on 4DCT data set of each patient. Dose of moving target vs. stationary target were simulated and compared for OARs and target by analyzing 3D dose and DVH(Dose Volume Histogram).There was almost 3.5% higher target maximum doses measured with moving target after applying the target motion trajectory data as compared to the stationary target whereas OARs doses were comparable. The results, clinically signifies the importance of motion management in lung tumors.